A dark and bloody ground the Hürtgen Forest and the Roer River dams, 1944-1945 - Miller, Edward G. 1958- (Texas A & M University military history series, 1995)
The book examines uncertainty of command at the army, corps, and division levels and emphasizes the confusion and fear of ground combat at the level of company and battalion-"where they do the dying." Its gripping description of the battle is based on government records, a rich selection of first-person accounts from veterans of both sides, and author Edward G. Miller's visits to the battlefield. The result is a compelling and comprehensive account of small-unit action set against the background of the larger command levels.